Ōe and beyond : fiction in contemporary Japan - Snyder, Stephen, 1957-; Gabriel, J. Philip (Book collections on Project MUSE., 1999)
Are the works of contemporary Japanese novelists, as Nobel Prize winner Oe Kenzaburo has observed, "mere reflections of the vast consumer culture of Tokyo and the subcultures of the world at large"? Or do they contain their own critical components, albeit in altered form? Oe and Beyond surveys the accomplishments of Oe and other writers of the postwar generation while looking further to examine the literary parameters of the "Post-Oe" generation. Despite the unprecedented availability today of the work of many of these writers in excellent English translations, some twenty years have passed since a collection of critical essays has appeared to guide the interested reader through the fascinating world of contemporary Japanese fiction. Oe and Beyond is a sampling of the best research and thinking on the current generation of Japanese writers being done in English. The essays in this volume explore such subjects as the continuing resonances of the atomic bombings; the notion of "transnational subjects"; the question of the "de-canonization" (as well as the "re-canonization") of writers; the construction (and deconstruction) of gender models; the quest for spirituality amid contemporary Japanese consumer affluence; post-modernity and Japanese "infantilism"; the intertwining connections between history, myth-making, and discrimination; and apocalyptic visions of fin de siecle Japan. Contributors pursue various methodological and theoretical approaches to reveal the breadth of scholarship on modern Japanese literature. The essays reflect some of the latest thinking, both Western and Japanese, on such topics as subjectivity, gender, history, modernity, and the postmodern. Oe and Beyond includes essays on Endo Shusaku, Hayashi Kyoko, Kanai Mieko, Kurahashi Yumiko, Murakami Haruki, Murakami Ryu, Nakagami Kenji, Oe Kenzaburo, Ohba Minako, Shimada Masahiko, Takahashi Takako, and Yoshimoto Banana. Contributors: Davinder L. Bhowmik, Philip Gabriel, Van C. Gessel, Adrienne Hurley, Susan J. Napier, Sharalyn Orbaugh, Jay Rubin, Atsuko Sakaki, Ann Sherif, Stephen Snyder, Mark Williams, Eve Zimmerman